2020
DOI: 10.1371/journal.pone.0242495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different cleaning procedures on water use and bacterial levels in weaner pig pens

Abstract: Pork is one of the most globally eaten meats and the pig production chain contributes significantly to the water footprint of livestock production. However, very little knowledge is available about the on-farm factors that influence freshwater use in the pig production chain. An experiment was conducted to quantify the effect of three different washing treatments on freshwater use, bacterial levels [(total bacterial counts; TBC), Enterobacteriaceae and Staphylococcus] and cleaning time in washing of pens for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…The considerable differences in LA-MRSA prevalence at 16 weeks between the two types may be due to thorough decontamination of bacteria from the previous fattening phase (type C&D). A well-performed C&D will reduce the bacterial microbial load by a factor of 10,000 [ 24 , 25 ]. This influence of the initial bacterial concentration at the time of stabling can be considered substantial and represents the only difference between the two groups of animals considered.…”
Section: Discussionmentioning
confidence: 99%
“…The considerable differences in LA-MRSA prevalence at 16 weeks between the two types may be due to thorough decontamination of bacteria from the previous fattening phase (type C&D). A well-performed C&D will reduce the bacterial microbial load by a factor of 10,000 [ 24 , 25 ]. This influence of the initial bacterial concentration at the time of stabling can be considered substantial and represents the only difference between the two groups of animals considered.…”
Section: Discussionmentioning
confidence: 99%
“…Trial 1 studied the influence of the dietary treatments (control diet [Ct], control diet + 3,000 ppm ZnO [Zn], and control diet + 100 ppm apramycin as Apralan G200 [Ab]). Trials 2 and 3 studied the same in-feed treatments in combination with different cleaning protocols ( Table 1 ) for the rooms that were part of another study ( 41 ). A detailed description of each trial is provided further below.…”
Section: Methodsmentioning
confidence: 99%
“…Among internal biosecurity measures to limit the persistence and proliferation of pathogenic bacteria in livestock buildings, cleaning and disinfection (C&D) protocols are applied between each breeding cycle. In addition to environmental and safety concerns associated with their use, several studies have shown that these chemical biocides are poorly effective on biofilms and only allow the elimination of a small fraction of the microbiota present on surfaces [ 3 , 60 , 61 ]. Hence, it has been shown in avian farms that C&D protocols are not totally effective in eradicating residual pathogens responsible for cross-contamination between different batches of animals such as Salmonella spp.…”
Section: Biosafety Tools For the Livestock Sectormentioning
confidence: 99%
“…biofilm with microbial pathogens. These biofilms can persist between two production batches despite the application of biosecurity measures [ 3 , 60 , 61 ]. After C&D protocols and before the entry of animals, positive bacteria can be sprayed on the building surface and material to colonize the “empty” biotope and help to prevent the settlement of undesirable microorganisms.…”
Section: Positive Biofilms To Protect Surfacesmentioning
confidence: 99%